A Predominance of Clade 17 Candida albicans Isolated From Hemocultures in a Tertiary Care Hospital in Thailand - Pham, Linh Thi Truc; Pharkjaksu, Sujiraphong; Chongtrakool, Piriyaporn; Suwannakarn, Kamol; Ngamskulrungroj, Popchai (Frontiers in Microbiology, 2019)
Candida albicans is one of the most common human fungal pathogens. Candidemia has significant mortality globally. No epidemiological study of C. albicans based on Multi Locus Sequence Typing (MLST) has been conducted in Thailand. Therefore, MLST was used to study the molecular epidemiology of C. albicans blood strains in a large Thai teaching hospital. In vitro virulence phenotypes and antifungal susceptibility testing by broth microdilution were also conducted. Forty-six C. albicans blood strains from thirty-seven patients were collected from the Department of Microbiology, Siriraj Hospital in 2016 and 2017. Most patients (71.8%) were more than 60 years old and the case fatality rate was 54.8%. Male to female ratio was 5:3. Thirty-four diploid sequence types (DSTs), including six new DSTs, were identified with DST2514 (8.7%) and DST2876 (8.7%) as the most common DSTs. Strains were clustered into nine clades. Unlike other studies of C. albicans blood strains in Asia, clade 17 was the most common (13 strains, 28.3%). Sequential allelic changes were evident in sequential strains from one patient. All strains produced phospholipase and hemolysin while none produced proteinase. The ability to form biofilm was found in 82.6% of the strains. Clade 17 strains showed significantly stronger hemolytic activity than non-clade 17 strains (69.2% versus 27.3%; p = 0.022). However, no significant association existed between clades and patients’ mortalities. All were susceptible or wild type to anidulafungin (MIC range = 0.015 – 0.12 and GM = 0.030), micafungin (MIC range = ≤ 0.008 – 0.015 and GM = 0.008), caspofungin (MIC range = 0.008 – 0.12 and GM = 0.036) and amphotericin B (MIC range = 0.25 – 0.5 and GM = 0.381). Only one strain was resistant to voriconazole (MIC range = ≤ 0.008 – ≥ 8 and GM = 0.010) and fluconazole (MIC range = 0.12 – 16 and GM = 0.398). In conclusion, a high prevalence of clade 17 C. albicans blood strains was found in Thailand, in contrast to other Asian countries. This unique finding might be explained by the strong hemolytic activity that is required for bloodstream infection of C. albicans.